2018
DOI: 10.1136/annrheumdis-2018-213286
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients with psoriatic and rheumatoid arthritis: data from the prospective multicentre NOR-DMARD study compared with Norwegian general population controls

Abstract: Health-related quality of life was overall similar in patients with RA and patients with PsA-with a tendency to worse scores in PsA-and worse compared with Norwegian general population controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
2
15
0
1
Order By: Relevance
“…This view that anxiety and depression are a less significant comorbidity in PsA has also recently been supported by two studies not included in the two review articles. In the study by Michelsen et al, HRQoL both for the SF-36 mental and the physical sum scores were significantly lower in PsA patients than in the background population [3]. However, the difference between PsA patients and controls was less for the mental (47.1 vs 50.0) than for the physical sum score (30.5 vs 50.0).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This view that anxiety and depression are a less significant comorbidity in PsA has also recently been supported by two studies not included in the two review articles. In the study by Michelsen et al, HRQoL both for the SF-36 mental and the physical sum scores were significantly lower in PsA patients than in the background population [3]. However, the difference between PsA patients and controls was less for the mental (47.1 vs 50.0) than for the physical sum score (30.5 vs 50.0).…”
Section: Discussionmentioning
confidence: 88%
“…The clinical presentation in psoriatic arthritis (PsA) is heterogeneous involving the musculoskeletal system, nails and skin, and other domains [ 1 ]. Health-related quality of life (HRQoL) has been shown to be impaired among patients with both psoriasis (PsO) [ 2 ] and PsA [ 3 ]; however, impairment has been shown to be greater in PsA [ 4 , 5 ]. For PsA patients to reach optimal improvement in HRQoL, improvement in both skin and musculoskeletal involvement must be achieved [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the disease on HRQoL is comparable to other diseases. In arthritis, a number of studies have demonstrated significantly lower quality of life compared to the general population both in patients with rheumatoid arthritis [33][34][35][36][37] and in those with psoriatic arthritis [38][39][40][41] . This underlines the need for new treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, both the psoriasis and the PsA disease are well documented to negatively affect HRQoL. 4 13–15…”
Section: Discussionmentioning
confidence: 99%